Cabotegravir, the Long-Acting Integrase Strand Transfer Inhibitor, Potently Inhibits Human T-Cell Lymphotropic Virus Type 1 Transmission in vitro - Schneiderman, Bethany S.; Barski, Michal S.; Maertens, Goedele N. (Frontiers in Medicine, 2022)
Human T cell Lymphotropic Virus Type 1 (HTLV-1) is a deltaretrovirus most prevalent in Southwestern Japan, sub-Saharan Africa, Australia, South America and the Carribean. Latest figures approximate 10 million people worldwide to be infected with HTLV-1. This is likely a significant underestimation due to lack of screening in endemic areas and absence of seroconversion symptoms. The two primary diseases associated with HTLV-1 infection are adult T cell leukaemia-lymphoma, a malignant and, sometimes, aggressive cancer; and HTLV-1 associated myelopathy/tropical spastic paraparesis, a debilitating neurological degenerative disease. Unfortunately, despite the poor prognosis, there is currently no effective treatment for HTLV-1 infection. We previously showed that integrase strand transfer inhibitors (INSTIs) clinically used for HIV-1 prophylaxis and treatment are also effective against HTLV-1 transmission in vitro. In 2021 a new INSTI, cabotegravir, was approved by the FDA for HIV-1 treatment. We thus set out to evaluate its efficacy against HTLV-1 infection in vitro. Strand transfer assays performed using recombinant HTLV-1 integrase treated with increasing concentrations of cabotegravir, effectively inhibited strand transfer activity, displaying an IC50 of 77.8 ± 22.4 nM. Furthermore, cabotegravir blocked HTLV-1 transmission in tissue culture; we determined an EC50 of 0.56 ± 0.26 nM, similar to bictegravir. Alu-PCR confirmed the block in integration. Thus, there are 4 INSTIs and 1 reverse transcriptase inhibitor approved by the FDA for HIV-1 treatment, that potently block HTLV-1 infection in vitro. This should strongly encourage the establishment of a new standard of HTLV-1 treatment – particularly for pre-exposure prophylaxis and prevention of mother-to-child transmission.